maximum value of 6y+10y
6y + 8 = 32 6y + 8 - 8 = 32 - 8 6y = 24 6y/6 = 24/6 y = 4
3x + 6y + 6x = 9x + 6y which can be factorised as 3(3x +2y)
Two ways to see this: 6y=8-9+6y 6y=6y-1 No answer here 6y= 8-(9+6y) 6y+(9+6y)=8 12y+9=8 12y=-1 y= -(1/12) or -0.08333...
(A) x + 6y = 19 (B) -x + 6y = 17 (A)+(B): 12y = 36 so that y = 3 Substituting this value of y in (A), x + 18 = 19 so x = 1.
4x+6y=62 -6x+6y=-18 what is the ordered pair
It does nothing! 4x + 6y = 24 7x + 6y = 9 Subtracting the first equation from the second gives: 3x = - 15 so that x = -5 Substituting the value of x in the first equation gives -20 + 6y = 24 so that 6y = 44 and so y = 22/3 or 71/3
Presumably this is a simultaneous question in which you're asked to find the values of x and y. x+6y = 55 -x+6y = 53 Adding both equations: 0+12y = 108 Divide both sides by 12 to find the value of y: y = 9 Substituting y = 9 into the original equation will enable you to find the value of x: x = 1 and y = 9
6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y
20+6y is the equation simplified, but there is no way to figure out the answer.
4x + 6y = 62-6x + 6y = -18 Multiply this equation by -1 the result will be_______________4x + 6y = 626x - 6y = 18_______________ Equation 1 + Equation 2 the result will be10x = 80 ----> X=8Put the value of X in one of the Equations above to find the value of yand so Y=5
The answer depends on the value of y. For example, when y = 0, 8y2 + 6y - 2 = -2 when y = 1, it is 12
-6y+3 = -7y+8 -6y+7y = 8-3 y = 5
That is the answer. If y is undefined, then 1+6y is as far as you can go.
16 = 6y +2 Yes
x(y - 10) + 6y
6y + 4.. i think
Rearrange the equations in the form of:- 6x-6y = 17-11 -4x+6y = 21 6x-6y = 6 -4x+6y = 21 Add both equatios together in order to eliminate y: 2x = 27 Divide both sides by 2: x = 13.5 Substitute the value of x into the equations to find the value of y: x = 13.5 and y = 12.5
The slope of -x plus 6y is equals to 12 is said to be (2 + 1/6x).
the simplest form of 5x + 3y +2x - 6y is 7x-3y
As written, that's 17y + 4 which is in its simplest form. -6y^2 + 23y + 4 factors to (4 - y)(1 + 6y)
One answer is : 6x+6y + wx+wy = (6+w)x + (6+w)y.